Splicing Characterization of CLCNKB Variants in Four Patients With Type III Bartter Syndrome - Wang, Chunli; Han, Yuan; Zhou, Jiaran; Zheng, Bixia; Zhou, Wei; Bao, Huaying; Jia, Zhanjun; Zhang, Aihua; Huang, Songming; Ding, Guixia; Zhao, Fei (Frontiers in Genetics, 2020)
Objective Type III Bartter syndrome (BS) is caused by loss-of-function mutations in the gene encoding basolateral chloride channel ClC-Kb (CLCNKB), and is characterized by hypokalemic metabolic alkalosis and hyperreninemic hyperaldosteronism. Here, we investigated the molecular defects in four Chinese children with clinical manifestations of Bartter syndrome. Methods The genomic DNA of the four patients was screened for gene variations using whole-exome sequencing (WES). The candidate variants were validated by direct Sanger sequencing. Quantitative PCR (qPCR) was subsequently performed to confirm the whole CLCNK gene deletion mutation. A minigene assay and reverse transcription PCR (RT-PCR) were performed to analyze the effect of splice variants in vitro. Results Our patients showed early onset age with hyponatremia, hypokalemia, hypochloremia, repeated vomiting and growth retardation, suggesting Bartter syndrome. Genetic analysis revealed that all patients carried compound heterozygous or homozygous truncating variants in the CLCNKB gene. In particular, we identified a novel nonsense variant c.239G > A (p.(Trp80*)), two splice site variants (c.1053-1 G > A and c.1228-2A > G), a whole gene deletion, and a novel synonymous variant c.228A > C (p.(Arg76Arg)) which located -2 bp from the 5′ splice donor site in exon 3. Furthermore, our in vitro minigene analysis revealed c.228A > C, c.1053-1G > A, and c.1228-2A > G cause the skipping of exon 3, exon 12, and exon 13, respectively. Conclusion Our results support that the whole CLCNKB gene deletion is the most common mutation in Chinese patients with type III BS, and truncating and whole gene deletion variants may account for a more severe phenotype of patients. We verified the pathogenic effect of three splicing variants (c.228A > C, c.1053-1G > A, and c.1228-2A > G) which disturbed the normal mRNA splicing, suggesting that splice variants play an important role in the molecular basis of type III BS, and careful molecular profiling of these patients will be essential for future effective personalized treatment options.